HUBUNGAN MEDIA POWER POINT DENGAN MINAT BELAJAR SISWA KELAS VII B SMP NEGERI 21 PONTIANAK - Fatmawati, Fatmawati; Okianna, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstrackThis research is motivated by the social studies learning process which currently teachers use learning media during learning and in accordance with the material taught, learning media in the process of teaching and learning activities is one of the supporting factors in increasing students' interest in learning. This study aimsed to determine whether there is a relationship between power point media usage and student learning interest in social studies learning at VII B Pontianak SMP Negeri 21. The data collection tool used a was questionnaire as the main method for collecting data about the use of power point media with student learning interests, in addition to interviews and documentation as supporting or complementary methods. The number of samples in this study were 38 students of class VII B at SMP Negeri 21 Pontianak. From the results of research on the use of power point media with students' interest in learning, it can be stated that correlation uses product moment (rxy) obtained by r = 0.68. Keywords : interest to learn, media power point